Impaired Vascular Endothelial Growth Factor A and Inflammation in Patients With Peripheral Artery Disease. (September 2014) - Gardner, Andrew W.; Parker, Donald E.; Montgomery, Polly S.; Sosnowska, Danuta; Casanegra, Ana I.; Esponda, Omar L.; Ungvari, Zoltan; Csiszar, Anna; Sonntag, William E.
We compared apoptosis, cellular oxidative stress, and inflammation of cultured endothelial cells treated with sera from 130 patients with peripheral artery disease (PAD) and a control group of 36 patients with high burden of comorbid conditions and cardiovascular risk factors. Second, we compared circulating inflammatory, antioxidant capacity, and vascular biomarkers between the groups. The groups were not significantly different ( P > .05) on apoptosis, hydrogen peroxide, hydroxyl radical antioxidant capacity, and nuclear factor κ-light-chain enhancer of activated B cells. Circulating tumor necrosis factor α (TNF-α; P = .016) and interleukin 8 (IL-8; P = .006) were higher in the PAD group, whereas vascular endothelial growth factor A (VEGF-A; P = .023) was lower. The PAD does not impair the endothelium beyond that which already occurs from comorbid conditions and cardiovascular risk factors in patients with claudication. However, patients with PAD have lower circulating VEGF-A than the control group and higher circulating inflammatory parameters of TNF-α and IL-8.